Correlation of Farmers Motivation to Cultivate Vegetables with Their Involvement atPeken Carik Activity in Subak Sembung, Peguyangan Village, North Denpasar Sub-district - DEVI, NI LUH GEDE NIRMALA; SARJANA, I DEWA GEDE RAKA; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Correlation of Farmers Motivation to Cultivate Vegetables with Their Involvement atPeken Carik Activity in Subak Sembung, Peguyangan Village, North Denpasar Sub-district Vegetables are one of the horticultural sub-sector plants which is amount cultivated bylots of farmers, one of them is farmers in Subak Sembung, Peguyangan Village, North Denpasar Sub-district. Subak Sembung developed into an ecotourism and has a supporting program known as peken carik activity. All of farmers in Subak Sembung are involved at peken carik activity and make it as an shopping tour media to sell vegetables to people which is in line with their motivation to cultivate vegetables. This research aims to determine the level of farmers motivation to cultivate vegetables, the level of farmers involvement at peken carik activity, and correlation between the farmers motivation to cultivate vegetables with their involvement at peken carik activity in Subak Sembung, Peguyangan Village, North Denpasar Sub-district. Sampling are 60 respondent using incidental method. The data were analyzed used qualitative analysis and quantitative analysis of Spearman rank correlation test.The result of qualitative analysis to describe the level of farmers motivation to cultivate vegetables was in high category, however the level of farmers involvement at peken carik activity was in very low category. The result of Spearman rank correlation test showed the correlation of farmer motivation to cultivate vegetables with their involvement at peken carik activity in Subak Sembung, Peguyangan Village, North Denpasar Sub-districtwas in low category.